2005
DOI: 10.1007/s00431-004-1547-1
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of coeliac disease in siblings of children with type 1 diabetes

Abstract: The 3.8% frequency of coeliac disease found in siblings of diabetic children is close to the 4.3% found previously in Czech children with type 1 diabetes mellitus and is substantially higher than the rate in the healthy children population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
(23 reference statements)
1
9
0
1
Order By: Relevance
“…The first study conducted by Hummel et al (6) showed the frequent occurrence of CD-associated antibodies in relatives. Consecutive studies have yielded similar results in that increased prevalence of biopsy-proven or serology-positive CD was found in relatives of diabetics (6,8,(10)(11)(12). Conversely, Saukkonen et al (9) reported similar prevalence of biopsy-proven CD and Jaeger et al (7) reported similar rates of seropositivity of IgAtTG positivity between first-degree relatives of T1DM and control groups, similar to our results.…”
Section: Statistical Analysessupporting
confidence: 80%
“…The first study conducted by Hummel et al (6) showed the frequent occurrence of CD-associated antibodies in relatives. Consecutive studies have yielded similar results in that increased prevalence of biopsy-proven or serology-positive CD was found in relatives of diabetics (6,8,(10)(11)(12). Conversely, Saukkonen et al (9) reported similar prevalence of biopsy-proven CD and Jaeger et al (7) reported similar rates of seropositivity of IgAtTG positivity between first-degree relatives of T1DM and control groups, similar to our results.…”
Section: Statistical Analysessupporting
confidence: 80%
“…This pattern is reminiscent of celiac disease (CD), an autoimmune disorder triggered by the ingestion of gluten in susceptible individuals. Overlap between both diseases has long been acknowledged, and the prevalence of (undiagnosed) CD within T1D and their relatives is higher than expected (199,313,414). Unlike in CD patients, however, there is no robust evidence to assume that gluten actually drives the initiation of autoimmunity in T1D (198).…”
Section: Wheat Proteinsmentioning
confidence: 97%
“…In association with various autoimmune disorders, wheat proteins and, more specifically, gluten, have received significant attention [98100]. Indeed, it has been demonstrated that a wheat-based diet induces not only Th1-type cytokine bias in the gut but also increased T-cell reactivity to gluten, with a higher frequency of diabetes [99101]. In addition to diabetes, it has been shown that celiac disease (CD) is associated with various extraintestinal autoimmune disorders that involve the thyroid, joints, heart, skin, pancreas, bone, liver, reproductive organs, and the nervous system [102112].…”
Section: Dietary Components and Autoimmunitiesmentioning
confidence: 99%